Plug-in Javascript [ 100 power solutions - Nixon, Robin , 1961- (McGraw-Hill, 2011)
"This practical resource contains 100 ready-to-run JavaScript plug-ins you can use to create dynamic Web content. The book begins by explaining JavaScript, Cascading Style Sheets (CSS) and the Document Object Model (DOM). Then, each chapter in Plug-In JavaScript offers complete, working examples for specific end results you can achieve right away. Using these plug-ins, you'll be able to build JavaScript projects quicker and easier than ever, as many complex tasks are reduced to a single function call. Get ready-made JavaScript plug-ins for: - Resizing and repositioning objects - Fading between objects - Movement and animation - Chaining and interaction - Menus and navigation - Text effects - Audio and visual effects - Cookies, Ajax, and security - Forms and validation - And much more Download all of the plug-ins at the book's companion website. "--Provided by publisher.